Broadening the Understanding and Linking Soil with Human Health: Key to Enhancing Relevance of Soil Science - S.P. Datta (Journal of the Indian Society of Soil Science, 2026)
I am highly grateful to the Indian Society of Soil Science, New Delhi, in general, and to Jorhat Chapter of Indian Society of Soil Science, Jorhat, in particular for providing me the opportunity to deliver the 21st Dr. R.R. Agrawal Memorial Lecture at Jorhat Agricultural University, Jorhat. Dr. Radha Raman Agarwal, an astute Agricultural Chemist and Director of Agriculture with unwavering interests in the management of soil resources for sustainable development. Dr. R.R. Agarwal left behind a rich scientific legacy as evident from his highly recognized contributions in soil inventory, soil fertility management as well as diagnosis and amelioration of soil sickness. Dr. Agarwal’s unwavering honesty, diligence and dedication to Soil Science research earned him well-deserved national and global recognition. Dr. Agrawal was President of Indian Society of Soil Science during 1962-63 and also served many prestigious organizations in different capacity. As we know that Soil Science has gradually been established as a distinct discipline in the whole arena of agriculture. At early age, scientists particularly having chemistry and geology background came forward and tried to understand various processes and properties of soil with their background knowledge. Also, over the years, meaningful attempts have been made to establish effective links of Soil Science with other disciplines of agriculture. But of late, Soil Science as discipline starts losing its shine and perhaps could not come up to the mark, where its all-round relevance should have been pronounced and established. In the backdrop of this contemporary scenario of the Discipline of Soil Science, I have chosen to speak on “Broadening the understanding and linking soil with human Health: key to enhancing relevance of soil Science” to pay my homage to this towering personality who contributed enormously to make this discipline relevant. To start with, it would not be of out of place to mention that the definition of human health as provided by the World Health Organization (WHO) as a state of complete physical, mental, and social well-being, and not merely the absence of disease or infirmity. This definition emphasizes that health encompasses more than just physical conditions; it includes emotional and social aspects as well. Additionally, health can be understood as the extent of an individual’s ability to cope with their environment, which includes physical, emotional, mental, and social dimensions. State of human health is intimately connected with the state of soil health.